The case against paramilitary policing considered - Waddington, Peter A. J. (The British journal of criminology, 1993)
Tony Jefferson's recent book, The Case against Paramilitary Policing Jefferson 1990 deserves serious consideration not only because it takes issue at length with a brief article written by me, but, more importantly, because it represents a powerful polemic against modern methods of police riot control. However, this polemic fails to convince for several reasons, both analytical and factual. This article will challenge Jefferson's thesis on four grounds: the definition of paramilitary' that is employed; the factual basis for the alleged strong correlation' between paramilitary policing and ensuing violence; the stance of viewing paramilitary policing from below'; and, finally, his criticism of the supposedly idealistic emphasis in my prescription of impartiality and restraint